Komunitas Ikan di Perairan Danau Wilayah Sulawesi Utara dan Gorontalo - Haryono Haryono (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2004)
The study of lake fishes community in North Sulawesi and Gorontalo provinces was done during July and August 2001. The lakes of study were Tondano (St.1), Moat (St.2), Tondok (St.3) and Limboto (St.4) under observation methods to determine the  fishes diversity, abundance, local distribution, status and economy values. There were  17 different species from 12 families screened during this study, the Cyprinidae was the dominant one  and consist of three  species. Overall  the variation of  fishes consist of eight  introducable species and nine native species. The most abundance species was Ophieleotris aporos  and the most wide distributed was Cyprinus carpio, mostly species have  economic values. Comparing to three other lakes, the Limboto has the  most various species of  fishes.